Ethnic Enclaves, Economic and Political Threat: An Investigation With the European Social Survey - Demireva, Neli; Zwysen, Wouter (Frontiers in Sociology, 2021)
This article examines the labor market outcomes and political preferences of majority, minority, or migrant individuals who report that they live in an ethnic enclave—a neighborhood with few majority residents. Politicians often proclaim that ethnic enclaves are problematic, but there is little rigorous examination of these claims. The ethnic composition of a local residential area can affect its inhabitants negatively by increasing conflict and competition (real or perceived) between groups. Majority members may feel their economic and political power questioned and think that the resources to which they are entitled have been usurped by newcomers. Migrants and minorities can be negatively impacted by isolation from the mainstream society, and their integration attempts can be hindered in ethnically concentrated local areas. Using data from the 2002 and 2014 waves of the European Social Survey, enriched with contextual data, we examine the impact of ethnic enclaves accounting for selection and compositional differences. We do not find evidence that minority concentrated areas impact negatively upon the economic outcomes of majority members, not even of those in precarious positions. We do however find that residence in enclaves is associated with greater propensity to vote for the far right and dissatisfaction with democracy for the majority group. Furthermore, there is an economic enclave penalty associated with the labor market insertion of migrants and the job quality of the second generation, and ethnic enclaves also increase the dissatisfaction with democracy among the second generation. We discuss our findings in light of the threat and contact literature.